Toxicity Screening and Hypocholesterolemic Effect Evaluation of Aqueous Extract of Anacardium occidentale Linn. in Hypercholesterolemic Induced Rabbits - Fazali Fazil,; Zulkhairi Amom,; Nurhaizan Mohd Esa,; Mohd Kamal Nik Hasan,; Khairul Kamilah Abdul Kadir,; Zamri Md Shah,; Shahidan Sulaiman, (International Journal of Phytomedicine, 2011)
Previous findings have supported to the ethnopharmacological use of Anacardium occidentale Linn. in folk medicine. In this study, the toxicity properties and the hypocholesterolemic effect of aqueous extract of Anacardium occidentale Linn. were evaluated in hypercholesterolemic induced rabbits. Thirty Five male New Zealand White Rabbits were randomly assigned into five groups and fed with normal diet (NC), 0.5% high cholesterol diet (PC), 0.5% high cholesterol diet+10 mg/kg simvastatin (SC), 0.5% high cholesterol diet+100 mg/kg AOE (AOE100) and 0.5% high cholesterol diet+200 mg/kg AOE (AOE200). The study duration was set for 12 weeks. In vitro toxicity study has been performed using brine shrimp lethality test and MTT assay to determine the LC50 and IC50 values respectively while in vivo toxicity study has been evaluated in hypercholesterolemic induced rabbits. Blood samples were withdrawn at week 0 and 12. Supplementation of 0.5% high cholesterol diet caused the elevation of TC, LDL and TG and also significantly rise (p<0.05) the level of liver enzymes compared to the normal control group. For in vitro toxicity screening, extracts demonstrated very low LC50 values and no IC50 value detected. For in vivo hypercholesterolemic induced rabbits, extracts were able to prevent the increment of liver enzymes: gammaglutamyl transferase, alkaline phosphatase, aspartate aminotransferase and alanine aminotransferase compared to positive control group. Aqueous extract of AO found to be not toxic and posses hypocholesterolemic and hepatoprotective effects in hypercholesteromic induced rabbits.